Limpasu Pericarpium : an Alternative Source of Antioxidant From Borneo with Sequential Maceration Method - Irfan Zamzani; Nita Triadisti (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2021)
Antioxidants are substances that can slow down the oxidation process of free radicals. Limpasu plant (Baccaurea lanceolata (Miq) Muell. Arg), an indigenous plant of Borneo, is a natural antioxidant source. The purpose of this study was to determine the antioxidant activity of the limpasu pericarpium extract. The extraction of the limpasu pericarpium was done by maceration method using solvents with increasing polarity ranging from n-hexane, ethyl acetate, and methanol. Antioxidant activities of the three extracts were measured by the DPPH and FRAP methods. The IC50 values of n-hexane, ethyl acetate, and methanol extracts, as well as quercetin using the DPPH method were 517,45 µg/mL, 530,64 µg/mL, 10,63 µg/mL and 6,83 µg/mL, respectively. Meanwhile, the IC50 values obtained from FRAP method were 198,96 µg/mL, 190,07 µg/mL, 661,36 µg/mL, and 7,09 µg/mL, respectively. The results revealed that the methanol extract is more potent than other extracts tested for antioxidant activity.